Miles Morales. Suspended - Reynolds, Jason (A Spider-man novel, 2023)
During Mile's in-school suspension, he finds himself in a fierce battle with a classmate turned insidious termite who is determined to destroy books and the Black and Brown history they contain, and only Miles can stop him.